CHALLENGES AND PROSPECTS OF SUSTAINABLE ENVIRONMENTALLY ORIENTED DEVELOPMENT OF TERRITORIAL COMMUNITIES IN THE UKRAINIAN CARPATHIANS (Coordinates of Public Administration, 2026)
This article offers a research-informed analysis of the challenges and prospects of sustainable environmentally oriented development of territorial communities in the Ukrainian Carpathians in the context of decentralisation, European integration and post-war recovery. The purpose is to summarise the current condition of mountain communities, identify the key constraints on their socio-economic and environmental capacity, and substantiate directions for improving local development policy by drawing on European approaches to supporting mountain areas. The methodological basis combines systemic and institutional approaches, comparative analysis of mountain-policy models, content analysis of legal acts and strategic documents, and synthesis of Ukrainian scholarly findings. The results indicate that, after the local government reform, Carpathian communities gained broader managerial and fiscal opportunities, yet their realisation is limited by staff shortages, misalignment between residents’ priority needs and local policy actions, demographic and migration shifts, and rising environmental risks intensified by the war. It is argued that strategic planning should integrate ecological limits and territorial potential, while linking infrastructure recovery with tourism and recreation development, support for small and medium-sized enterprises, the formation of ecological culture, and fiscal equalisation instruments that reflect mountain specificities. A definition is proposed in which sustainable environmentally oriented community development is understood as a purposeful, long-term set of governance actions aimed at improving quality of life while preserving natural capital and ensuring intergenerational justice. It is concluded that strengthening the capacity of Carpathian communities requires institutional reinforcement of local governance, deeper partnerships with EU communities, and the implementation of adapted European practices for mountain-area support.